Highways and urban areas stormwater runoff: Main source of contamination by metals in the cascata brook-Botucatu (SP) - Belluta, Ivalde [UNESP]; Coelho, José Carlos [UNESP]; de JESUS, Sílvio Alexandre [UNESP]; de CARVALHO, Lídia Raquel [UNESP]; Wondracek, Marcos Henrique Pereira; de CASTRO, Gustavo Rocha [UNESP]; Doyama, Júlio Toshimi [UNESP] (UNESP - Universidade Estadual Paulista, 2020)
Metal species found at the sediments of water network may reveal a historical record of contamination. The objectives of this study were to quantify the metals Cd, Pb, Cu, Co, Cr, Ni, Zn and Sb in the sediments, to compare them with the results found in soils in the same area, to evaluate their relationship with the organic matter and the metal effects on the biota at the intersections of the Domingos Sartori (S1) and Marechal Rondon (S2) highways with the Cascata Brook. The determination of the metal species was performed using an atomic emission spectrometer with inductively coupled plasma. The results were statistically evaluated using Mann Whitney test. According to the results, the concentrations were in the range from 1.1 to 8.2 times higher in P2 than in P1. The relation between metal and organic matter index is in the decreasing order of concentration: Zn>Cu>Co>Cr>Ni>Pb>Cd. Only Sb was not detected in the samples. The guide values TEL and PEL of CONAMA and contamination factor presented order of contamination Cd>Cu>Zn, indicating the effect of toxicity on the riparian ecosystem, in almost all subsits of highways. The results are the basis for monitoring the stormwater runoff quality of urban areas and highways for the purpose of conserving and protecting the Cascata Brook.
Stormwater runoff de rodovias e áreas urbanas: Fonte principal de contaminação por metais no córrego da cascata – Botucatu (SP)
Keywords: Guiding values; Riparian ecosystems; Sediments; Subwatershed; Toxicity